ICCREM 2018. proceedings of the International Conference on Construction and Real Estate Management 2018, August 9-10, 2018, Charleston, South Carolina - Wang, Yaowu; Zhu, Yimin (Construction management professor); Shen, Qiping; Al-Hussein, Mohamed (American Society of Civil Engineers, 2018)
This collection contains 33 peer-reviewed papers on innovative technology and intelligent construction presented at the International Conference on Construction and Real Estate Management 2018, held in Charleston, South Carolina, August 9-10, 2018. Topics include: lean construction; information management modeling; BIM; project safety management; and construction industrialization.